Readability research in policy documents (2004-2024): a bibliometric analysis of trends, themes, authors, and international collaboration - Nordin, Noli Maishara; Ariffin, Kamisah; Mat Pardi, Khalid; Rostam Affendi, Faiza (Universiti Teknologi MARA, Perlis, 2025)
Readability plays a vital role in documentation to ensure that the targeted readers and the public understand the shared information. Readable documents allow readers to comprehend unfamiliar texts easily, hence helping them make informed decisions. Past studies have shown that documents related to law, finance, business, medical, nursing, and insurance policies, among others, often need clarification for laymen to comprehend the context due to the technical jargon used. To achieve a clearer insight into the readability of policy documents, this study conducts a bibliometric analysis of research articles from 2004 to 2024, exploring the research trends, significant contributors, prominent subject areas, themes, and countries’ collaboration in the research field. The finding reveals that the published articles' trend fluctuated and peaked in 2020 during the COVID-19 pandemic. Essential analysis of the key authors and their cited articles, popular research topics, keywords, and international cooperation networks are also highlighted. It is suggested that future research on readability in public documents should be expanded to broader geographical areas, studying different cultures and norms that affect readability and thus enhance global policy communication.